Impact of Full Veneer Crown Restoration on the Periodontal Health of Posterior Teeth - Salma, Mst Ummay; Rahman, Mohammad Arifur; Jannath, Fatema; Sultana, Nihar; Hossain, Mohammad Anayet (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Background: Periodontal health plays a vital role in the longevity of prosthodontic restorations. Full veneer crown (FVC) is one of the most common modalities in restoration of single tooth for preservation of function and health of oral tissues. Objectives : The study was done to critically evaluate the impact of FVC restoration providing standard procedures on the periodontal health of posterior teeth, also to observe the changes of periodontal health in terms of their status of gingival index, plaque index, periodontal pocket depth, bleeding on probing in different stages of treatment. Materials & Methods: This prospective study evaluated the impact of FVC on periodontal health of 30 endodontically treated posterior teeth with FVC and 30 contralateral natural teeth of 19 patients in different stages of treatment for 2 years duration in the Dept. of Prosthodontics, Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital. To assess the periodontal health gingival index, plaque index, periodontal pocket depth, bleeding on probing were used. Collected data were analyzed using SPSS software (version 22) according to the study Objectives Results: The study Result showed that the mean differences of gingival index and plaque index between abutments and contraleteral natural teeth were non significant (p > 0.05) at baseline, 4th month visit; but the differences were significant (p < 0.05) at 8th month, 12th month visits. Regarding periodontal pocket depth the mean differences between abutments and contraleteral natural teeth found non significant (p > 0.05) throughout the follow up period. Same thing observed in bleeding on probing except 12th month follow up visit, where highly significant (p < 0.01) mean differences observed. Also the study found that the gingival index, plaque index, bleeding on probing, periodontal pocket depth increased a bit in 4th,8th,12th month visits gradually in abutments, which was almost same in contralateral natural teeth in case of gingival index, periodontal pocket depth; and increased a bit in case of plaque index, bleeding on probing. Conclusion : If the FVC is fabricated maintaining all standard procedures equigingival margin with proper marginal adaptation, oral hygiene as well as general health of the patient is maintained although less but there is a chance of detrimental effects on periodontal health in comparison to contralateral natural teeth. J Bangladesh Coll Phys Surg 2023; 41: 46-52